Historical sources as ideas for creating fiction films “Simpang Masa: The imaginary meeting among Ronggowarsito, Mangkunegoro IV, and Raden Saleh” - Subiyanto Subiyanto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The 19th century was a turbulent time for the island of Java, especially for the Javanese inhabitants, who had just survived a devastating conflict known as the Java War (1825-1830). The policies of the newly established Dutch East Indies government (1818-1942) affected the Javanese. The 19th century was a turbulent time for the island of Java, especially for the Javanese inhabitants, who had just survived a devastating conflict known as the Java War (1825-1830). The policies of the newly established Dutch East Indies government (1818-1942) affected the Javanese experiencing a decline in self-confidence and a sharp recession in their socioeconomic, political, and cultural. Key historical figures: Raden Ngabehi Ronggowarsito (1802-73); Mangkunegoro IV (1811-81; reign 1853-81); and Raden Saleh Syarif Bustaman (around 1811-1880) came of age in this epoch. The research aims to use historical data as the idea of creation, Simpang Masa. Simpang Masa means Intersection of time In English. A historical approach is used to analyze the available primary and secondary data and to constitute a metaphorical approach for reading art through the prism of these three hugely talented figures. The way they interacted resulted in: (1) A heightened social awareness, which can be seen in the way their thought processes responded to contemporary social conditions; (2) A deepened aesthetic awareness, which enabled them to respond creatively to their environment and contemporary circumstances through their work; and (3) An enhanced spiritual awareness, which informed their individual and collective initiatives to protect Java’s circumstance. With a depth understanding of Javanese history, the history of the three selected individuals, and their artwork, the research will be able to capture the spirit and zeitgeist of the 19th century